Adverse Events and Complications in Continuous Intra-arterial Nimodipine Infusion Therapy After Aneurysmal Subarachnoid Hemorrhage - Kapapa, Thomas; König, Ralph; Mayer, Benjamin; Braun, Michael; Schmitz, Bernd; Müller, Silwia; Schick, Julia; Wirtz, Christian Rainer; Pala, Andrej (Frontiers in Neurology, 2022)
Objective To determine the frequencies and severity of complications associated with continuous intra-arterial infusion of nimodipine (CIANI) as a new treatment of Delayed Cerebral Ischemia (DCI) after aneurysmatic Subarachnoid Hemorrhage (SAH), we retrospectively evaluated data of 718 patients from two centers. Methods Patients treated on SAH between 2008 and 2016 were included. Frequencies of adverse events (AE), complications, their detailed characterization and severity (mild, moderate and severe) were evaluated, relative risk methods were used with the level of significance at p≤0.05. Clinical outcome was analyzed using Glasgow Outcome Scale (GOS). Unfavorable outcome was defined as GOS 1 to 3, favorable outcome as GOS 4 to 5. The Short-Form 36 (SF-36) health-related quality of life questionnaire severed as quality of life measurement. Results Out of 718 patients, 65 (9%) were treated by CIANI and had a higher clinical or imaging grad of bleeding severity. Clinical deterioration during the treatment course happened more often in patients treated with CIANI than in others. 67% of patients treated by CIANI had adverse events and/or complications during the treatment. Nimodipine-associated hypotension was seen in 8% (mild). Catheter associated thrombus occurred in 9% (moderate). New intracerebral hemorrhage was found in 14% (moderate). 6% treated by CIANI died during the treatment period (severe). More than one third (38.5%) of patients in CIANI cohort reached at least moderate disability and 23.1% showed good recovery. Patients after CIANI have reduced quality of life (QoL) based on SF-36 questionnaire, but differences in mental and general health, and pain were minimal. The relative risk for unfavorable outcome in those patients is 1,3 (CI 0.97 – 1.62, p=0.049) compared to other patients with SAH. Conclusion CIANI is related to higher rates of adverse events and complications compared to standard treatment of SAH. However, in those selected cases of CIANI patients with severe and therapy-refractory DCI CIANI is beneficial for outcome.